Preparation method of high-sensitivity catechol electrochemical detection electrode
By constructing D-FeCu-MOF/N,S-MQD@rGO composites, the salt resistance and self-stacking problems of MXene in electrochemical detection are solved, and high-sensitivity catechol detection is achieved, with excellent detection Performance and stability.
Patent Information
- Application Number
- CN202411453359.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, MXene has poor salt resistance and is prone to self-stacking, which limits its application in electrochemical detection, especially in terms of detection capabilities.
Defect engineering strategy is used to construct a bimetallic organic frame hybrid material D-FeCu-MOF rich in crystal defects, and is compounded with MXene quantum dots (N, S-MQD) and graphene (rGO) to form D-FeCu-MOF/ N,S-MQD@rGO composite material used to modify electrodes to enhance their electrocatalytic activity and charge/proton transfer rate.
Realizes high sensitivity catechol electrochemical detection, with a wide linear range, low detection limit, excellent anti-interference ability, good repeatability and reproducibility, and good test stability, suitable for actual samples Test.
Smart Images

Figure CN119224082A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical sensors, and in particular relates to a method for preparing a highly sensitive catechol electrochemical detection electrode. Background Art
[0002] Catechol, also known as catechol, is a key phenolic isomer of dihydroxybenzene. It plays a vital role in many production fields such as medicine, pesticides, food additives, cosmetics, rubber and antioxidants, and is widely used as a raw material and synthetic intermediate. However, its inherent high toxicity and difficult to degrade properties pose a serious threat to human health and the ecological environment. Therefore, achieving accurate quantitative detection of catechol is crucial to prevent its potential harm to the ecosystem and human health.
[0003] So far, a variety of detection methods have been reported for the detection of catechol, including synchronous fluorescence, chromatography, and mass spectrometry. However, these methods generally have limitations such as high cost, cumbersome pretreatment procedures, and complex operations. In this context, electrochemical sensors have become a highly anticipated detection method due to their high sensitivity, excellent selectivity, low cost, and rapid response. In order to construct a high-performance electrochemical sensor for catechol, it is particularly important to design electrode materials with excellent electrocatalytic properties.
[0004] Compared with traditional MOFs (metal organic frameworks), BMOFs (bimetal organic frameworks) can efficiently integrate the advantages of each MOFs by connecting two different types or the same type of MOFs materials, showing more abundant active sites, excellent physicochemical stability and unique bimetallic synergistic effects, thus showing a broader application potential in the field of electrochemistry. However, the poor conductivity of BMOFs itself limits its wide application in the field of electrocatalysis. In response to this challenge, a bimetallic organic framework hybrid material D-FeCu-MOF (D stands for defect) rich in crystal defects was successfully constructed by adopting a defect engineering strategy. By introducing defect engineering, the electronic structure of FeCu-MOF can be effectively adjusted, its conductivity can be improved, more unsaturated metal catalytic active sites can be exposed, and the reaction energy barrier can be reduced. Therefore, defective BMOFs materials are expected to become high-performance electrocatalytic materials.
[0005] MXene (molecular formula: Mn+1XnTx, where M represents transition metal, X represents carbon / nitrogen element, and T represents oxygen-containing group) is a typical two-dimensional layered carbon material. Due to its excellent electrical conductivity, adjustable surface properties and good hydrophilicity, it has shown broad application prospects in many fields such as catalysis, energy, environment and biology. However, MXene has poor salt tolerance, and its strong π-π* interaction easily leads to serious self-stacking phenomenon, thereby reducing its performance. In order to maintain and improve the performance of MXene, MXene quantum dots (MQDs, less than 10nm in size) derived from MXene have been found through research. MQDs not only retain the original advantages of MXene, but also show characteristics such as ultra-high surface-to-volume ratio and abundant edge defect sites under the action of size effect. However, the small size of MQDs leads to large intrinsic interactions and easy self-aggregation, which limits its detection ability. Therefore, a method for preparing a highly sensitive electrochemical detection electrode for catechol is proposed to solve the above problems. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a highly sensitive catechol electrochemical detection electrode to solve the problems raised in the above background technology.
[0007] To achieve the above object, the present invention provides the following technical solution: A method for preparing a highly sensitive catechol electrochemical detection electrode, comprising the following steps:
[0008] S1. Dissolve 0.80 mmol H3BTC in 20 mL of the mixed solution, then add 0.2 mL HAc and sonicate for 1 h to obtain solution A;
[0009] Then disperse 1.43 mmol Cu(NO3)2·3H2O in 10 mL distilled water to obtain solution B;
[0010] Solution A was stirred continuously, and solution B was added dropwise during the stirring process. Stirring was continued at room temperature for 15 min to obtain a clear blue solution. The solution was transferred to a reaction kettle and kept at 100 °C for 7 h. After cooling to room temperature, the solution was washed by centrifugation with ethanol and water to obtain a blue precipitate, which was dried at 80 °C for 12 h to obtain D-Cu(BTC);
[0011] S2. 16 mg of D-Cu(BTC) was dissolved in 20 mL of DMF solution and ultrasonicated for 1 h to obtain suspension A. 17.7 mg of NH2-BDC was dispersed in 20 mL of EtOH and 0.75 mL of HAc was injected into the above solution. The above solution was continuously stirred for 2 h to obtain solution B.
[0012] The suspension A was added to the solution B and stirred for 1 h. Then, 48 mg F-127 and 53 mg FeCl 3·6H2O were added to the above suspension and stirred for 2 h to form a mixture. Subsequently, the mixture was transferred to a reactor and heated at 110 °C for 12 h. The precipitate was collected by centrifugation and washed with a preset solution for multiple times until the pH of the solution was neutral. The precipitate was vacuum dried to obtain a green precipitate D-FeCu-MOF.
[0013] S3. Preset masses of Cys, UA, and MXene were uniformly dispersed in 10 mL of water and ultrasonically dispersed under nitrogen for 2 h to obtain a uniform suspension;
[0014] The mixture was then poured into a reactor to react under preset reaction conditions, then cooled to room temperature, filtered through a filter membrane, and then centrifuged at 10,000 rpm for 30 min. Finally, the yellow solution was poured into a dialysis bag and dialyzed for two days to obtain N,S-MQD, which was stored at 4°C for subsequent use.
[0015] S4. 20 μL of N,S-MQD solution was dispersed in 10 mL of rGO solution and ultrasonically dispersed for 4 h, aged at room temperature for 24 h, and then the suspension was centrifuged and washed three times with distilled water, and then freeze-dried to obtain black powder N,S-MQD@rGO;
[0016] S5. 10 mg of D-FeCu-MOF and 10 mg of N,S-MQD@rGO were dissolved in 10 mL of distilled water and ultrasonicated for 2 h to obtain a uniform suspension. After standing at room temperature for 24 h, the suspension was washed with distilled water and freeze-dried to obtain a D-FeCu-MOF / N,S-MQD@rGO composite material.
[0017] S6. Disperse 2 mg of the composite material obtained in S5 in 750 μL of Nafion solution and ultrasonicate for 30 min. Take 8 μL of the dispersed mixture and drop it on the pretreated GCE and let it stand at room temperature to dry.
[0018] Preferably, in S3, the reaction temperature of the preset reaction conditions is 160° C., and the reaction time is 12 h.
[0019] Preferably, in S3, the preset mass of Cys is 50 mg, the preset mass of UA is 50 mg, and the preset mass of MXene is 100 mg.
[0020] Preferably, in S4, the suspension is centrifuged at a rate of 10,000 rpm for 10 min.
[0021] Preferably, in S3, the filtration accuracy of the filtration membrane is 0.22 μm.
[0022] Preferably, in S2, the preset solution includes distilled water or ethanol.
[0023] Preferably, in S4, the concentration of the rGO solution is 1 mg / mL.
[0024] Preferably, in S1, the mixed solution is a mixed solution of ethanol and DMF, and the ratio of ethanol to DMF is 1:1.
[0025] A highly sensitive electrochemical detection electrode for catechol is prepared by the above preparation method, with a D-FeCu-MOF / N,S-MQD@rGO modified electrode as a working electrode, a graphite electrode or a platinum wire electrode as a counter electrode, and an Ag / AgCl electrode as a reference electrode.
[0026] A method for applying a highly sensitive catechol electrochemical detection electrode comprises applying the detection electrode to measure the concentration of catechol.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The D-FeCu-MOF / N,S-MQD@rGO composite material-based electrochemical sensor prepared by the present invention has more active electrocatalytic activity and faster charge / proton transfer rate, and exhibits excellent electrochemical sensing performance for CC detection: a wide linear range of 0.004-520 μM, a low detection limit of 0.0014 μM, excellent anti-interference ability, good repeatability and reproducibility, and good test stability. In actual sample detection, the prepared sensor also exhibits a good recovery rate of 98.23-102.67%, proving that it has the potential for application in actual situations. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 a and Figure 1 b SEM and TEM images of D-Cu(BTC), respectively;
[0030] Figure 2 a and Figure 2 b TEM images and b TEM images of D-FeCu-MOF, respectively;
[0031] Figure 3 TEM image of N,S-MQD@rGO;
[0032] Figure 4 SEM images of D-FeCu-MOF / N,S-MQD@rGO and the corresponding mapping images;
[0033] Figure 5Electrochemical impedance spectroscopy of FeCu-MOF, D-FeCu-MOF, rGO, N,S-MQD, D-FeCu-MOF / rGO, D-FeCu-MOF / N,S-MQD, N,S-MQD@rGO and D-FeCu-MOF / N,S-MQD@rGO in 5 mM [Fe(CN)6]3- / 4- solution containing 0.1 M KCl;
[0034] Figure 6 Schematic diagram of DPV curves for CC detection of D-FeCu-MOF / N,S-MQD@rGO in 0.1M pH=7.0 PBS in the concentration range of 50 to 250 μM;
[0035] Figure 7 Schematic diagram of DPV curve of continuous detection of CC by D-FeCu-MOF / N,S-MQD@rGO in 0.1M pH=7.0 PBS;
[0036] Figure 8 Schematic diagram of DPV curves of D-FeCu-MOF / N,S-MQD@rGO in 0.1M PBS (pH=7.0) for detecting 100μM CC and 1000μM interfering substances: NaCl, KCl, tryptophan (Trp), bisphenol A (BPA), phenol (PN), uric acid (UA), paracetamol (PAT), resorcinol (RF), tyrosine (Tyr) and guanosine nucleoside (GUA) in sequence;
[0037] Fig. 9 It graph of D-FeCu-MOF / N,S-MQD@rGO continuously tested in 0.1M PBS (pH=7.0) containing 10μM CC for 24h;
[0038] Fig.10 It is a bar graph of the long-term stability test of D-FeCu-MOF / N,S-MQD@rGO;
[0039] Fig.11 Schematic diagram of the DPV curve of the same D-FeCu-MOF / N,S-MQD@rGO electrode tested 7 times at 250μM CC;
[0040] Fig.12 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] See also Figure 1-Figure 12 As shown, the present invention provides the following technical solutions:
[0043] Implementation Method 1
[0044] This embodiment provides a method for preparing a highly sensitive catechol electrochemical detection electrode, and the specific steps are as follows:
[0045] Preparation of D-Cu(BTC):
[0046] 0.80 mmol H3BTC was dissolved in a mixed solution of 20 mL ethanol and DMF (ratio 1:1), and then 0.2 mL HAc was added and ultrasonicated for 1 hour to obtain solution A. 1.43 mmol Cu(NO3)2·3H2O was dispersed in 10 mL distilled water to obtain solution B. While stirring solution A, solution B was slowly added dropwise and stirred continuously at room temperature for 15 minutes to obtain a clear blue solution. The solution was transferred to a reactor and kept at 100°C for 7 hours. After cooling, it was centrifugally washed with ethanol and water and dried at 80°C for 12 hours to obtain D-Cu(BTC).
[0047] Preparation of D-FeCu-MO:
[0048] 16 mg D-Cu(BTC) was dissolved in 20 mL DMF and ultrasonicated for 1 hour to obtain suspension A. 17.7 mg NH2-BDC was dispersed in 20 mL EtOH, and 0.75 mL HAc was added and stirred for 2 hours to obtain solution B. Suspension A was added to solution B and stirred for 1 hour. 48 mg F-127 and 53 mg FeCl3·6H2O were added and stirred for 2 hours. The mixture was transferred to a reactor and heated at 110°C for 12 hours. The precipitate was collected by centrifugation, washed with distilled water and ethanol until the pH was neutral, and dried in vacuo to obtain D-FeCu-MO.
[0049] Preparation of N,S-MQD:
[0050] 50 mg Cys, 50 mg UA and 100 mg MXene were evenly dispersed in 10 mL water and ultrasonically dispersed under nitrogen for 2 hours. The mixed solution was poured into a reactor and reacted at 160 °C for 12 hours. After cooling, it was filtered through a 0.22 μm filter membrane and centrifuged at 10000 rpm for 30 minutes. The yellow solution was poured into a dialysis bag and dialyzed for two days to obtain N,S-MQD, which was stored at 4 °C.
[0051] Preparation of N,S-MQD@rGO:
[0052] 20 μL of N,S-MQD solution was dispersed in 10 mL of 1 mg / mL rGO solution, ultrasonically dispersed for 4 hours, aged and allowed to stand at room temperature for 24 hours, and the suspension was centrifuged at 10,000 rpm for 10 minutes, washed three times with distilled water, and freeze-dried to obtain black powder N,S-MQD@rGO.
[0053] Preparation of D-FeCu-MOF / N,S-MQD@rGO composites:
[0054] 10 mg D-FeCu-MOF and 10 mg N,S-MQD@rGO were dissolved in 10 mL distilled water and ultrasonicated for 2 h to obtain a uniform suspension. After standing at room temperature for 24 h, the suspension was washed with distilled water and freeze-dried to obtain a composite material.
[0055] Preparation of detection electrodes:
[0056] 2 mg of the composite material was dispersed in 750 μL of Nafion solution and ultrasonicated for 30 minutes. 8 μL of the dispersed mixed solution was dropped on the pretreated GCE and allowed to stand and dry at room temperature.
[0057] Implementation Method 2
[0058] This embodiment is basically the same as the first embodiment, but differs in the steps of preparing N,S-MQD:
[0059] When preparing N,S-MQD, the preset masses of Cys, UA, and MXene were adjusted to 60 mg, 60 mg, and 120 mg, respectively, and the other steps remained unchanged.
[0060] Implementation Method 3
[0061] This embodiment is basically the same as the first embodiment, but differs in the steps of preparing D-FeCu-MO:
[0062] In the preparation of D-FeCu-MO, the masses of F-127 and FeCl3·6H2O were adjusted to 55 mg and 60 mg, respectively, and the other steps remained unchanged.
[0063] Implementation Method 4
[0064] This embodiment provides a preparation method based on different solvent systems:
[0065] Preparation of D-Cu(BTC):
[0066] 0.80 mmol H3BTC was dissolved in a mixed solution of 20 mL acetone and DMF (ratio 1:1), 0.2 mL HAc was added, and solution A was obtained by ultrasonication for 1 hour.
[0067] The subsequent steps are the same as those in the first embodiment.
[0068] Preparation of D-FeCu-MO, N,S-MQD, N,S-MQD@rGO, D-FeCu-MOF / N,S-MQD@rGO composite materials and detection electrodes:
[0069] The subsequent steps are the same as those in the first embodiment.
[0070] Implementation Method 5
[0071] This embodiment provides a preparation method based on different drying methods:
[0072] Preparation of D-Cu(BTC) to D-FeCu-MO:
[0073] The steps are the same as those in the first embodiment.
[0074] Preparation of N,S-MQD:
[0075] The steps are the same as those in the first embodiment, but vacuum drying is used instead of freeze drying after dialysis.
[0076] Preparation of N,S-MQD@rGO:
[0077] 20 μL of N,S-MQD solution was dispersed in 10 mL of rGO solution, ultrasonically dispersed for 4 hours, aged and allowed to stand at room temperature for 24 hours, the suspension was centrifuged, washed three times with distilled water, and then vacuum dried to obtain black powder N,S-MQD@rGO.
[0078] Preparation of D-FeCu-MOF / N,S-MQD@rGO composite materials and detection electrodes:
[0079] The subsequent steps are the same as those in the first embodiment.
[0080] Implementation Method 6
[0081] This embodiment provides a preparation method based on different electrode materials:
[0082] Preparation of D-Cu(BTC) to D-FeCu-MO:
[0083] The steps are the same as those in the first embodiment.
[0084] Preparation of N,S-MQD to preparation of N,S-MQD@rGO:
[0085] The steps are the same as those in the first embodiment.
[0086] Preparation of D-FeCu-MOF / N,S-MQD@rGO composites:
[0087] 10 mg of D-FeCu-MOF and 15 mg of N,S-MQD@rGO were dissolved in 10 mL of distilled water and ultrasonicated for 2 h to obtain a uniform suspension.
[0088] The subsequent steps are the same as those in the first embodiment.
[0089] Preparation of detection electrodes:
[0090] 2 mg of the composite material was dispersed in 750 μL of Nafion solution and ultrasonicated for 30 minutes. 8 μL of the dispersed mixture was dropped on the pretreated platinum wire electrode and allowed to stand and dry at room temperature.
[0091] Implementation Method 7
[0092] This embodiment provides a preparation method based on different ultrasonic treatment times:
[0093] Preparation of D-Cu(BTC) to D-FeCu-MO:
[0094] The steps are the same as those in the first embodiment.
[0095] Preparation of N,S-MQD:
[0096] 50 mg of Cys, 50 mg of UA and 100 mg of MXene were uniformly dispersed in 10 mL of water and ultrasonically dispersed under nitrogen for 3 hours (different from 2 hours in the first embodiment) to ensure more complete dispersion.
[0097] The subsequent steps are the same as those in the first embodiment.
[0098] Preparation of N,S-MQD@rGO:
[0099] 20 μL of N,S-MQD solution was dispersed in 10 mL of 1 mg / mL rGO solution and ultrasonically dispersed for 6 hours (different from 4 hours in the first embodiment) to enhance the interaction between N,S-MQD and rGO.
[0100] The subsequent steps are the same as those in the first embodiment.
[0101] Preparation of D-FeCu-MOF / N,S-MQD@rGO composite materials and detection electrodes:
[0102] The subsequent steps are the same as those in the first embodiment.
[0103] Implementation Method 8
[0104] This embodiment provides a method for preparing a composite material based on different reaction temperatures:
[0105] Preparation of D-Cu(BTC) to D-FeCu-MO:
[0106] The steps are the same as those in the first embodiment.
[0107] Preparation of N,S-MQD to preparation of N,S-MQD@rGO:
[0108] The steps are the same as those in the first embodiment.
[0109] Preparation of D-FeCu-MOF / N,S-MQD@rGO composites:
[0110] 10 mg of D-FeCu-MOF and 10 mg of N,S-MQD@rGO were dissolved in 10 mL of distilled water and ultrasonicated for 2 hours. Then, the mixture was allowed to stand at 120° C. (different from the room temperature in the first embodiment) for 24 hours to promote better bonding of the components in the composite material.
[0111] The subsequent washing and drying steps are the same as those in the first embodiment.
[0112] Preparation of detection electrodes:
[0113] The subsequent steps are the same as those in the first embodiment.
[0114] Implementation Method 9
[0115] This embodiment provides a preparation method based on different electrode modification methods:
[0116] Preparation of D-Cu(BTC) to D-FeCu-MO:
[0117] The steps are the same as those in the first embodiment.
[0118] Preparation of N,S-MQD to preparation of N,S-MQD@rGO:
[0119] The steps are the same as those in the first embodiment.
[0120] Preparation of D-FeCu-MOF / N,S-MQD@rGO composites:
[0121] The subsequent steps are the same as those in the first embodiment.
[0122] Preparation of detection electrodes:
[0123] 2 mg of the composite material was dispersed in 1 mL of Nafion solution (different from 750 μL in the first embodiment) and ultrasonicated for 30 minutes.
[0124] Then, the dispersed mixed solution was evenly coated on the pretreated GCE by drop coating, rather than directly adding it. After coating, it was left to dry at room temperature to form a more uniform modified layer.
[0125] Implementation Method 10
[0126] This embodiment provides an electrode preparation method based on different pretreatment methods:
[0127] Electrode pretreatment:
[0128] Before preparing the detection electrode, the GCE was polished to remove surface impurities and oxides. Then, the GCE was immersed in ethanol for 10 minutes for ultrasonic cleaning, then rinsed with distilled water, and finally dried under nitrogen to ensure the cleanliness and flatness of the electrode surface.
[0129] Preparation of D-Cu(BTC) to D-FeCu-MO:
[0130] The steps are the same as those in the first embodiment.
[0131] Preparation of N,S-MQD to preparation of N,S-MQD@rGO:
[0132] The steps are the same as those in the first embodiment.
[0133] Preparation of D-FeCu-MOF / N,S-MQD@rGO composite materials and detection electrodes:
[0134] The subsequent steps are the same as those in the first embodiment, but before adding the composite material solution, the pretreated GCE is first activated, such as by using cyclic voltammetry scanning, to improve the electrochemical activity of the electrode.
[0135] Application Method
[0136] The detection electrodes obtained in all embodiments can be used to measure the concentration of catechol. In order to study the value of D-FeCu-MOF / N,S-MQD@rGO-based electrochemical sensors in practical applications, the standard addition method can be used to perform real sample detection of catechol (CC) in lake water samples. The specific steps include water sample pretreatment, standard solution addition, recovery determination, etc., to ensure that the recovery rate is between 98.23-102.67%, and the relative standard deviation (RSD) is 1.01-2.89%, in order to verify the accuracy and application potential of the electrochemical sensor.
[0137] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a highly sensitive catechol electrochemical detection electrode, characterized in that: The steps include: S1. 0.80 mmol H3BTC was dissolved in 20 mL of the mixed solution, and then 0.2 mL HAc was added and ultrasonicated for 1 h to obtain solution A; Then, 1.43 mmol Cu(NO3)2·3H2O was dispersed in 10 mL distilled water to obtain solution B; Solution A was stirred continuously, and solution B was added dropwise during the stirring process. Stirring was continued at room temperature for 15 min to obtain a clear blue solution. The solution was transferred to a reaction kettle and kept at 100 °C for 7 h. After cooling to room temperature, the solution was washed by centrifugation with ethanol and water to obtain a blue precipitate, which was dried at 80 °C for 12 h to obtain D-Cu(BTC); S2. 16 mg of D-Cu(BTC) was dissolved in 20 mL of DMF solution and ultrasonicated for 1 h to obtain suspension A. 17.7 mg of NH2-BDC was dispersed in 20 mL of EtOH and 0.75 mL of HAc was injected into the above solution. The above solution was continuously stirred for 2 h to obtain solution B. The suspension A was added to the solution B and stirred for 1 h. Then, 48 mg F-127 and 53 mg FeCl3·6H2O were added to the suspension and stirred for 2 h to form a mixture. Subsequently, the mixture was transferred to a reactor and heated at 110°C for 12 h. The precipitate was collected by centrifugation and washed with a preset solution for multiple times until the pH of the solution was neutral. The precipitate was vacuum dried to obtain a green precipitate D-FeCu-MOF. S3. Preset masses of Cys, UA, and MXene were uniformly dispersed in 10 mL of water and ultrasonically dispersed under nitrogen for 2 h to obtain a uniform suspension; The mixture was then poured into a reactor to react under preset reaction conditions, then cooled to room temperature, filtered through a filter membrane, and then centrifuged at 10,000 rpm for 30 min. Finally, the yellow solution was poured into a dialysis bag and dialyzed for two days to obtain N,S-MQD, which was stored at 4°C for subsequent use. S4. 20 μL of N,S-MQD solution was dispersed in 10 mL of rGO solution and ultrasonically dispersed for 4 h, aged at room temperature for 24 h, and then the suspension was centrifuged and washed three times with distilled water, and then freeze-dried to obtain black powder N,S-MQD@rGO; S5. 10 mg of D-FeCu-MOF and 10 mg of N,S-MQD@rGO were dissolved in 10 mL of distilled water and ultrasonicated for 2 h to obtain a uniform suspension. After standing at room temperature for 24 h, the suspension was washed with distilled water and freeze-dried to obtain a D-FeCu-MOF / N,S-MQD@rGO composite material. S6. Disperse 2 mg of the composite material obtained in S5 in 750 μL Nafion solution and ultrasonicate for 30 min. Take 8 μL of the dispersed mixture and drop it on the pretreated GCE. Let it stand and dry at room temperature to obtain D-FeCu-MOF / N,S-MQD@rGO modified electrode.
2. The method for preparing a highly sensitive catechol electrochemical detection electrode according to claim 1, characterized in that: In S3, the reaction temperature of the preset reaction conditions is 160° C., and the reaction time is 12 h.
3. The method for preparing a highly sensitive catechol electrochemical detection electrode according to claim 1, characterized in that: In S3, the preset mass of Cys is 50 mg, the preset mass of UA is 50 mg, and the preset mass of MXene is 100 mg.
4. The method for preparing a highly sensitive catechol electrochemical detection electrode according to claim 1, characterized in that: In S4, the suspension is centrifuged at a rate of 10,000 rpm for 10 min.
5. The method for preparing a highly sensitive catechol electrochemical detection electrode according to claim 1, characterized in that: In S3, the filtration accuracy of the filtration membrane is 0.22 μm.
6. The method for preparing a highly sensitive catechol electrochemical detection electrode according to claim 1, characterized in that: In S2, the preset solution includes distilled water or ethanol.
7. The method for preparing a highly sensitive catechol electrochemical detection electrode according to claim 1, characterized in that: In S4, the concentration of the rGO solution is 1 mg / mL.
8. The method for preparing a highly sensitive catechol electrochemical detection electrode according to claim 1, characterized in that: In S1, the mixed solution is a mixed solution of ethanol and DMF, and the ratio of ethanol to DMF is 1:
1.
9. A highly sensitive electrochemical detection electrode for catechol, characterized in that: The D-FeCu-MOF / N,S-MQD@rGO modified electrode prepared by the preparation method described in any one of claims 1 to 8 is used as the working electrode, the graphite electrode or the platinum wire electrode is used as the counter electrode, and the Ag / AgCl electrode is used as the reference electrode.
10. An application method of a highly sensitive catechol electrochemical detection electrode, characterized in that: Includes the application of detection electrodes in measuring the concentration of catechol.
